Treating seronegative neuromyelitis optica spectrum disorder with inebilizumab: a case report - Lehrieder, Dominik; Zapantis, Nikolaos; Pham, Mirko; Schuhmann, Michael Klaus; Haarmann, Axel (Frontiers in Neurology, 2023)
Background Neuromyelitis optica spectrum disorder (NMOSD) is a devastating inflammatory disease of the central nervous system that is often severely disabling from the outset. The lack of pathognomonic aquaporin 4 (AQP4) antibodies in seronegative NMOSD not only hinders early diagnosis, but also limits therapeutic options, in contrast to AQP4 antibody-positive NMOSD, where the therapeutic landscape has recently evolved massively. Case presentation We report a 56-year-old woman with bilateral optic neuritis and longitudinally extensive myelitis as the index events of a seronegative NMOSD, who was successfully treated with inebilizumab. Conclusion Treatment with inebilizumab may be considered in aggressive seronegative NMOSD. Whether broader CD19-directed B cell depletion is more effective than treatment with rituximab remains elusive.